EFFICACY OF NICOTIANA PLUMBAGINIFOLIA (SOLANACEAE) LEAF EXTRACTS AS LARVICIDE AGAINST MALARIAL VECTOR ANOPHELES STEPHENSI LISTON 1901 - ANIKET SINGH; KUNTAL BHATTACHARYA; GOUTAM CHANDRA (International Journal of Pharma and Bio Sciences, 2015)
The best way to control mosquito borne diseases is to control the mosquito population. The present study was executed to evaluate the mosquito larvicidal activity of Nicotiana plumbaginifolia leaves against malarial vector Anopheles stephensi.Crude extracts and three different solvent extracts were bio-assayed against An. stephensi larvae. LC50 and LC90 values were determined appropriately. Qualitative phytochemical tests were also done. Statistical justifications were drawn through Log-probit, regression and ANOVA analyses. Effects of bio-active fractions on some of the non-target water fauna were also examined. Crude extract was considerably mosquito larvicidal. Only ethyl acetate extractives exhibited larvicidal activity amongst all solvent extractives. Cent percent mortality of 1st, 2nd and 3rd instars larvae was noticed within 72 h at 50 ppm concentration. Leaves contained tannins, steroids and flavonoids. Non-target organisms were non-responsive to bioactive fractions. N. plumbaginifolia leaves bear the potentiality to control An. stephensi larvae in a target specific way.